155 Fracture of Pubic Rami During Hip Fracture Fixation - a Rare Case of Traction Table Related Injury. (28th February 2022) - Gomindes, A.R.; Remtulla, M.; Mohammed, A.; Cooper, J.; Nikolaidis, A.
Abstract: Background: Traction tables form the mainstay of closed reduction techniques for lower limb fracture and in particular hip fractures. They offer a versatile solution to continuous traction required in a variety of operations such as closed intramedullary femoral fixation and hip fixation. Counter traction on the table is provided by the perineal post, this has been associated with significant complications such as neuropraxia, erectile dysfunction, cutaneous necrosis, and urethral injuries. Case presentation: We present a case of an elderly and co-morbid patient who was scheduled to undergo a hip fracture fixation using an intramedullary nail. Unfortunately, this was delayed by 3 weeks as the patient was unfit to undergo this procedure. She was placed onto the traction table and intra-operatively sustained a superior and inferior pubic rami fracture while attempting reduction on the traction table. Conclusions: Closed reduction techniques using traction tables and perineal posts are not without morbidity. Risk factors such as osteoporosis and delayed fixation should be accounted for when managing this complex and often frail group of patients.